Evaluation Of Apical Sealing Ability of Ah Plus, Mta Fillapex And Bioceramic Sealer – An In Vitro Study. - Chougule, Prajakta Ganesh; Karagir, Amol (Journal of Neonatal Surgery, 2025)
Aim – The present study aimed to compare apical sealing ability between AH Plus, MTA Fillapex and Bioceramic sealer. Materials and method – Eighty extracted human maxillary anterior teeth with fully formed apex and straight root were collected for this study. The root canals were cleaned and shaped using a standard step-back preparation to size 60# master apical file at the established working length and divided into four groups: Group 1 – AH plus sealer with gutta-percha; Group 2 – MTA fillapex sealer with gutta-percha; Group 3 – Bioceramic sealer with gutta-percha; Group 4 – Positive control group (teeth were obturated without sealer). Dye leakage was carried out. Statistical analysis was done using the Statistical Package for the Social Sciences software and ANOVA test. Results: The Bioceramic sealer group had a mean leakage of 1.39mm, MTA Fillapex had a mean leakage of 1.52 mm, whereas AH Plus had a mean of 2.68 mm. The standard deviations of AH Plus, MTA Fillapex and bioceramic sealer were 0.71, 0.77 and 0.39, respectively. ANOVA disclosed no significant difference (P < 0.05) between the groups. Conclusion: None of the sealers used in the study could completely seal the apical foramen to have a fluid‑tight seal. AH Plus, MTA Fillapex and bioceramic sealer showed no statistically significant difference in microleakage; the better result was shown by bioceramic sealer